Perioral Dermatitis after Dental Filling in a 12-Year-Old Girl: Involvement of Cholinergic System in Skin Neuroinflammation? - Fabrizio Guarneri; Herbert Marini (The Scientific World Journal)
The etiopathogenesis of perioral dermatitis (PD) is still unknown and, consequently, medical treatment is difficult, not precisely defined, and often unsatisfactory. On the basis of a peculiar case that appeared soon after multiple dental fillings with a mercury-containing amalgam, we proposed that neurogenic inflammation could play a role in the pathogenesis of PD. According to the new findings provided by clinical and basic research, neurogenic inflammation has a relevant part in the pathogenesis of many cutaneous diseases. We report a similar case of PD, taking into account, more specifically, the possible involvement of the cholinergic system. Also in this case, PD seems to be mainly related to the mercury contained in dental fillings and/or its organic compounds formed by oral/gut bacteria. We examined the possible role of these substances as causes of PD, providing new information on the possible cross-talk between neuroimmunodermatology and potential triggers of PD.